ANCIENT CITIES OF SUGHD AND ITS RECEPTION IN HISTORY AND CULTURE - Isamiddinov , M. (EurasianUnionScientists, 2020)
The article describes the history of the ancient cities of Sughd, based on archeological and written sources. In particular, the urban culture of Sughd in the VII century BC, the development of cities in the Achaemenid period was systematically studied on the example of Kuktepa and Afrosiab.